Estimation of an asymmetric model of asset prices - Harvey, A; Shephard, N (American Statistical Association, 1996)
A stochastic volatility model may be estimated by a quasi-maximum likelihood procedure by transforming to a linear state-space form. The method is extended to handle correlation between the two disturbances in the model and applied to data on stock returns.